Simulation-Based Optimization of Cure Cycle of Large Area Compression Molding for LED Silicone Lens - Min-Jae Song; Kwon-Hee Kim; Seok-Kwan Hong; Jeong-Won Lee; Jeong-Yeon Park; Gil-Sang Yoon; Heung-Kyu Kim (Advances in Materials Science and Engineering)
Three-dimensional heat transfer-curing simulation was performed for the curing process by introducing a large area compression molding for simultaneous forming and mass production for the lens and encapsulants in the LED molding process. A dynamic cure kinetics model for the silicone resin was adopted and cure model and analysis result were validated and compared through a temperature measurement experiment for cylinder geometry with cure model. The temperature deviation between each lens cavity could be reduced by implementing a simulation model on the large area compression mold and by optimizing the location of heat source. A two-step cure cycle was constructed to reduce excessive reaction peak at the initial stage and cycle time. An optimum cure cycle that could reduce cycle time by more than 29% compared to a one-step cure cycle by adjusting dwell temperature, heating rate, and dwell time was proposed. It was thus confirmed that an optimization of large area LED lens molding process was possible by using the present experiment and the finite element method.